Proceedings of the International Conference of Ethics on Business, Economics, and Social Science (ICEBESS 2018) 2019
DOI: 10.2991/icebess-18.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Income Smoothing Determinants in Indonesia Banking Industry

Abstract: The research aims to determine the effect of profitability, corporate value, company size and financial risk to income smoothing. Researchers would like to review the factors affecting income smoothing, at the banking companies listed on the IDX during the period of 2014-2016. The sampling method use author is purposive sampling there are 21 company of research sample or 66 sample. The analysis technique used is logistic regression with enter method and quartile analysis. The results showed profitability, corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Previous studies has examine income smoothing using profitability (Artawan et al, 2020;Arum & Aminah, 2017;Fitri et al, 2018;Fitriani, 2018;Gunawan & Hardjunanto, 2020;Haniftian & Dillak, 2020;Herdjiono et al, 2019;Indrawan & Damayanthi, 2020;Oktaviasari et al, 2018;Oktoriza, 2018;Oktyawati & Agustia, 2014;Peranasari & Dharmadiaksa, 2014;Sellah & Herawaty, 2019;Setyaningtyas & Hadiprajitno, 2014;Yanti & Dwirandra, 2019), firm size (Arum & Aminah, 2017;Benandri & Andayani, 2018;Fitri et al, 2018;Fitriani, 2018;Gunawan & Hardjunanto, 2020;Indiraswari & Rahmayanti, 2022;Indrawan & Damayanthi, 2020;Lahaya, 2017;Lim, 2022;Nathania & Nugroho, 2023;Nugraha & Dillak, Julianti, 2018;Oktaviasari et al, 2018;Oktoriza, 2018;Peranasari & Dharmadiaksa, 2014;Setyaningtyas & Hadiprajitno, 2014;Sunetri et al, 2022), firm risks (Benandri & Andayani, 2018;Lahaya, 2017;Leviany et al, 2019;Masning et al, 2022;Peranasari & Dharmadiaksa, 2014), dividend policy (Bobby et al, 2022;…”
Section: Profitability Firm Value Income Smoothing: the Moderating Ro...unclassified
See 1 more Smart Citation
“…Previous studies has examine income smoothing using profitability (Artawan et al, 2020;Arum & Aminah, 2017;Fitri et al, 2018;Fitriani, 2018;Gunawan & Hardjunanto, 2020;Haniftian & Dillak, 2020;Herdjiono et al, 2019;Indrawan & Damayanthi, 2020;Oktaviasari et al, 2018;Oktoriza, 2018;Oktyawati & Agustia, 2014;Peranasari & Dharmadiaksa, 2014;Sellah & Herawaty, 2019;Setyaningtyas & Hadiprajitno, 2014;Yanti & Dwirandra, 2019), firm size (Arum & Aminah, 2017;Benandri & Andayani, 2018;Fitri et al, 2018;Fitriani, 2018;Gunawan & Hardjunanto, 2020;Indiraswari & Rahmayanti, 2022;Indrawan & Damayanthi, 2020;Lahaya, 2017;Lim, 2022;Nathania & Nugroho, 2023;Nugraha & Dillak, Julianti, 2018;Oktaviasari et al, 2018;Oktoriza, 2018;Peranasari & Dharmadiaksa, 2014;Setyaningtyas & Hadiprajitno, 2014;Sunetri et al, 2022), firm risks (Benandri & Andayani, 2018;Lahaya, 2017;Leviany et al, 2019;Masning et al, 2022;Peranasari & Dharmadiaksa, 2014), dividend policy (Bobby et al, 2022;…”
Section: Profitability Firm Value Income Smoothing: the Moderating Ro...unclassified
“…;Herdjiono et al (2019);Nugraha & Dillak, Julianti (2018);Oktaviasari et al (2018); Oktoriza (2018); Oktyawati & Agustia (2014); Peranasari & Dharmadiaksa (2014); Yanti & Dwirandra (2019)suggested that profitability is positively associated with income smoothing. Arum & Aminah (2017); Natalie & Astika (2016); Nurani & Dillak (2019) found that profitability is negatively associated with income smoothing.…”
mentioning
confidence: 99%